The functional significance of the autolysis loop in protein C and activated protein C - Yang, Likui; Manithody, Chandrashekhara; Rezaie, Alireza R. (Thrombosis and Haemostasis, 2005)
The autolysis loop of activated protein C (APC) is five residues longer than the autolysis loop of other vitamin K-dependent coagulation proteases. To investigate the role of this loop in the zymogenic and anticoagulant properties of the molecule, a protein C mutant was constructed in which the autolysis loop of the protein was replaced with the corresponding loop of factor X. The protein C mutant was activated by thrombin with ~5-fold higher rate in the presence of Ca2+. Both kinetics and direct binding studies revealed that the Ca2+ affinity of the mutant has been impaired ∼3-fold. The result of a factorVa degradation assay revealed that the anticoagulant function of the mutant has been improved 4–5-fold in the absence but not in the presence of protein S. The improvement was due to a better recognition of both the P1-Arg506 and P1-Arg306 cleavage sites by the mutant protease. However, the plasma half-life of the mutant was markedly shortened due to faster inactivation by plasma serpins. These results suggest that the autolysis loop of protein C is critical for the Ca2+-dependence of activation by thrombin. Moreover, a longer autolysis loop in APC is not optimal for interaction with factor Va in the absence of protein S, but it contributes to the lack of serpin reactivity and longer half-life of the protease in plasma.
Keywords: Activated protein C; thrombin; thrombomodulin; factorVa; antithrombin